Seasonal flow reversals of intermediate waters in the canary current system east of the canary Islands - Machín, Francisco; Pelegrí, Josep L.; Fraile-Nuez, E.; Vélez-Belchí, P.; López-Laatzen, F.; Hernández-Guerra, A. (Journal of Physical Oceanography, 2010)
Two 9-yr current-meter and salinity records, together with climatological data, reveal marked seasonal variability of the intermediate flow at a key location in the Canary Basin. The region is characterized by a summer (July–September) and early fall (October) northward progression of Antarctic Intermediate Water followed by a fall (November–December) intense flow reversal of Mediterranean Water. A Sverdrup-type model confirms that these movements are associated with stretching or shrinking of the intermediate water strata.